PEDOT:PSS‐Assisted Exfoliation and Functionalization of 2D Nanosheets for High‐Performance Organic Solar Cells. (3rd July 2017) - Xing, Wang; Chen, Yusheng; Wu, Xiaoxi; Xu, Xiaozhou; Ye, Pan; Zhu, Ting; Guo, Qingyu; Yang, Liqiu; Li, Weiwei; Huang, Hui
Abstract : Here, a facial and scalable method for efficient exfoliation of bulk transition metal dichalcogenides (TMD) and graphite in aqueous solution with poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) to prepare single‐ and few‐layer nanosheets is demonstrated. Importantly, these TMD nanosheets retain the single crystalline characteristic, which is essential for application in organic solar cells (OSCs). The hybrid PEDOT:PSS/WS2 ink prepared by a simple centrifugation is directly integrated as a hole extraction layer for high‐performance OSCs. Compared with PEDOT:PSS, the PEDOT:PSS/WS2 ‐based devices provide a remarkable power conversion efficiency due to the "island" morphology and benzoid–quinoid transition. This study not only demonstrates a novel method for preparing single‐ and few‐layer TMD and graphene nanosheets but also paves a way for their applications without further complicated processing. Abstract : A novel PEDOT:PSS/2D nanosheets ink as hole extraction layer is used to fabricate high‐performance organic solar cells. 2D nanosheets with single‐ and few‐layer structure exist stably in the ink because of PEDOT:PSS exfoliation and functionalization. The enhanced power conversion efficiency arises from the "island" morphology and benzoid–quinoid transition upon addition of 2D nanosheets.